O processo de criação do programa Universidade para Todos - PROUNI - Guerra, Lenin Cavalcanti Brito (2009)
From the end of the 80s, the Brazilian higher education experience strong growth, coming from the private sector, which would intensify further in the late 90th Higher education has become a lucrative business. With a drop in the number of students entering and strong competition, the number of idle places in private institutions of higher education reached 49.5% in 2004. That same year, by Measure, was the University for All Program (PROUNI) program, to include high school students from public higher education, offering scholarships to those students in private HEIs. In exchange, the IES gain tax exemption. The objective of this research is to investigate the game of interest occurred in the formulation of this program and identify the model and the political game and has led to the creation of PROUNI, analyzing the process occurred since the wording of a bill, the issue of Measure Law and that the legitimacy PROUNI, with the most important changes made initial model. Since the first draft of the Law to the final Act, the PROUNI was disfigured in its main points, as the percentage of stock for paying students, the process of selection of stock and bond of the IES program. Throughout the process of creating the program, it is quite clear the performance of the institutions representing the private higher education. As reference for the analysis was based on Rational Choice Theory of Political Science. The basic argument of the methods based on rational choice is the maximization of the benefit will be the main motivation of individuals, but they can give that your goals can be achieved more effectively through institutional action and thereby discover that their conduct is shaped by institutions. Thus, individuals rationally choose to get to a certain extent constrained to join in certain institutions, whether voluntarily or not. The PROUNI was submitted by government and public policy covered by the mystical aura of the discourse of social justice and economic development, as in higher education includes a stratum of people who would not have access to the university, due to restrictions in the supply network public higher education. However, the greatest benefit from the program are the private HEIs, which through a difficult time in a scenario marked by high competition and idleness of nearly half of the vacancies offered. The PROUNI became a program that prioritizes access and not the residence of the student to higher education. More serious than a supporting program for students Fellows is a program supporting the institutions of private education